Збалансоване харчування – запорука безпечної життєдіяльності - Четова, Д. С.; Катковнікова, Л. А. (Національний технічний університет "Харківський політехнічний інститут", 2021)
Проведено аналіз умов, що впливають на харчування, яке забезпечує здоровий спосіб життя. Наведено складові, що відносяться до здорового харчування. Зазначено, що наявність необхідної кількості вітамінів – запорука успішного метаболізму у людини.

The analysis of conditions affecting nutrition, which provides a healthy lifestyle. The components related to a healthy diet are given. The results of recent studies show that vitamins by mechanism of action are divided into vitamins and vitamin-like substances. It is noted that the presence of the necessary amount of vitamins is the key to successful metabolism in humans.
Balanced nutritionis the key to safe living
Keywords: безпека життєдіяльності; здорове харчування; life safety; healthy eating